2020
DOI: 10.1073/pnas.2005476117
|View full text |Cite
|
Sign up to set email alerts
|

Estimating unobserved SARS-CoV-2 infections in the United States

Abstract: By March 2020, COVID-19 led to thousands of deaths and disrupted economic activity worldwide. As a result of narrow case definitions and limited capacity for testing, the number of unobserved severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections during its initial invasion of the United States remains unknown. We developed an approach for estimating the number of unobserved infections based on data that are commonly available shortly after the emergence of a new infectious disease. The logic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 51 publications
(51 reference statements)
3
53
0
3
Order By: Relevance
“…According to these scenarios, the RT–PCR testing policy in Slovakia was able to trace approximately 11% of all infected individuals in the population for the given period. A similar situation was in China, Italy or in the USA, where scientists projected that the number of confirmed cases in hotspots could oscillate between 10 and 20% of all infected people [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 78%
“…According to these scenarios, the RT–PCR testing policy in Slovakia was able to trace approximately 11% of all infected individuals in the population for the given period. A similar situation was in China, Italy or in the USA, where scientists projected that the number of confirmed cases in hotspots could oscillate between 10 and 20% of all infected people [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 78%
“…The Pearson correlation coefficient is 0.76, indicating a general agreement in trend. A recent study estimated that 108,689 (95% CI: 1023 to 14,182,310) infections occurred in the United States before 12 March 2020 ( 41 ). Our inference estimated 236,207 (95% CI: 193,855 to 298,937) total infections in the United States by that date, which is within the CI and in line with the magnitude of the best estimate from that study.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed methodology is, to the best of our knowledge, the first method to propose an optimal spatio-temporal allocation of limited test-kit resources. A first study for the estimate of unobserved COVID-19 infections [5] in the USA indicated that early testing would have decreased the surveillance gap during a critical phase of the epidemic. More recently a number of studies have emerged that address the optimal allocation of resources.…”
Section: Discussionmentioning
confidence: 99%
“…While there is valuable information being gathered, their estimates rely on testing individuals that are either already symptomatic or have been selected based on certain criteria (hospital visits, airport arrivals, geographic vicinity to researchers, etc.). Generic, randomized tests of the population are broadly applied but they have been hampered either by delays [5] or by insufficient numbers of test kits [6]. There is broad recognition that efficient testing strategies are critical for the timely identification of infectious individuals and the optimal allocation of resources [7].…”
Section: Introductionmentioning
confidence: 99%